2021
DOI: 10.1155/2021/7647718
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Complexity of Business Information Dissemination in Social Media: A Meta‐Analysis of Empirical Evidence from China

Abstract: With the development of social networks, the complexity of the factors affecting the users’ information dissemination is increasing and the complexity of online social networks and influencing factors of individual behaviors and attitudes make the development of online public opinion present a dynamic, complex, and multifactor evolution. Analyzing the influencing factors of public opinion dissemination is conducive to optimize company management and information diffusion management. However, there has been no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Jin et al (2016) found an association between information quality and the likelihood of adopting health-care information. Additionally, according to Yan et al (2021), perceived information quality positively impacts individuals' information adoption behavior. Therefore, this study argues that when the information presented to customers is considered high quality, customers will assess the consequences of the actions more favorably, leading to a higher likelihood of adoption.…”
Section: Perceived Information Quality and Information Adoptionmentioning
confidence: 99%
“…Jin et al (2016) found an association between information quality and the likelihood of adopting health-care information. Additionally, according to Yan et al (2021), perceived information quality positively impacts individuals' information adoption behavior. Therefore, this study argues that when the information presented to customers is considered high quality, customers will assess the consequences of the actions more favorably, leading to a higher likelihood of adoption.…”
Section: Perceived Information Quality and Information Adoptionmentioning
confidence: 99%
“…Fission communication is a widely mentioned and recognized mode of communication in the field of communication, which is also considered to be called viral communication by virtue of its fastspreading speed and wide influence. Microblogging, shaking sound such social media through the attraction of the content, can be without the influence of external driving force so that users spontaneously generate sharing, commenting and other behaviors so that the information can be the fastest speed, the largest range of diffusion [27][28].…”
Section: Digital Information Dissemination Mode Of Film and Televisio...mentioning
confidence: 99%
“…76 As one of the basic functions of PVC, information sharing involves the exchange of useful information such as ideas, opinions, news and experiences in PVC. 77 Generally, people select and judge information according to their own needs, and then adopt, use and share information based on the perception of information utility. 55 This process of using information purposeful is considered as a social behavior of sharing resources.…”
Section: Information Sharing Of Professional Virtual Communitymentioning
confidence: 99%